Torque and Power Consumption of Paddlewheel Aerator With Movable Blade - Samsul Bahri (Malikussaleh University, 2015)
The development of movable blade is based on fact that power is required only when blade of paddle wheel aerator entering water and in contrary action of aeration effect only when the blade is about leaving the water. This study was carrier out to design and simulate paddle wheel aerator with movable blade which will open when entering water and close when leaving water. Wheel closed at quadrant I to IV (entering water surface) and was about to open at quadrant III to II (leaving water surface). The blade was designed referring to commonly used Taiwan wheel type. The component of mobable blade mechanism consisted of cam and shaft, velg, velg cap, blade holder, follower, spring and bearing. Follower was able rotate with angle of rotation was 125°, rotational displacement was 50 mm, maximum velocity was 0.55 m/s and acceleration was 6.09 m/s2. Testing without a load at 115 rpm shows the torque that occured 43.05 N and the electric power used 511.72 Watt. The gain is smaller than the increase of torque and power needed for movable blade paddlewheel aerator mechanism